2013
DOI: 10.1021/cg4009224
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Moisture and Thermal Stability of Metal–Organic Frameworks through Incorporation of Pendant Hydrophobic Groups

Abstract: An isostructural series of NbO-type porous metal-organic frameworks (MOFs) with different dialkoxy-substituents of formula Cu 2 (TPTC-OR) (TPTC-OR = 2',5'-di{alkyl}oxy-[1,1':4',1''-terphenyl]-3,3'',5,5''-tetracarboxylate, R = Me, Et, n Pr, n Hex) has been synthesized and characterized. The moisture stability of the materials has been evaluated and a new superhydrophobic porous MOF has been identified. The relationship between pendant side chain length and thermal stability has been analyzed by in situ synchrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 63 publications
1
77
1
Order By: Relevance
“…The BET surface areas are higher than previous reported 1855 m 2 g -1 [36] of Cu 2 TPTC-Me and 1127 m 2 g -1 [41] of Cu 2 TPTC-OMe, which could be attributed to the difference of activated processes and computational methods [22]. is comparable to those in other MOFs with the same copper paddlewheels [44].…”
Section: Resultscontrasting
confidence: 42%
See 2 more Smart Citations
“…The BET surface areas are higher than previous reported 1855 m 2 g -1 [36] of Cu 2 TPTC-Me and 1127 m 2 g -1 [41] of Cu 2 TPTC-OMe, which could be attributed to the difference of activated processes and computational methods [22]. is comparable to those in other MOFs with the same copper paddlewheels [44].…”
Section: Resultscontrasting
confidence: 42%
“…Cu 2 TPTC-Me and Cu 2 TPTC-OMe were solvothermally synthesized similarly to the literatures [36,41]. Organic linkers H 4 TPTC-Me and H 4 TPTC-OMe were synthesized via Suzuki coupling reaction followed by hydrolysis and acidification (Scheme S1).…”
Section: Synthesis Of Cu 2 Tptc-me and Cu 2 Tptc-omementioning
confidence: 99%
See 1 more Smart Citation
“…29−31 To date, some studies have reported the functionalization of the parent NOTT series materials, including tuning the moisture and thermal stability and introduction of mesopores. 32,33 However, it appears to be almost ignored that the MOFs exhibit excellent CO 2 adsorption properties, especially under ambient temperature and pressure. The incorporation of polar groups like amino or hydroxy into the organic linkers is more favorable for the enhancement of CO 2 uptake through increasing interactions of CO 2 molecules with the framework of MOFs, and a higher selectivity of CO 2 upon other permanent gases may be achieved thereupon.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs synthesized from some tritopic, tetratopic, and octatopic carboxylic acid ligands have also shown characteristics of hydrophobicity . Cai et al reported two Cu 2 paddle‐wheel SBU based MOFs, [Cu 3 (mbtc) 2 ] (CuMBTC) and [Cu 3 (ebtc) 2 ] (CuEBTC), which were obtained from methyl‐ and ethyl‐ group‐functionalized H 3 btc ligands, H 3 mbtc and H 3 ebtc, respectively .…”
Section: Preparation Of Hydrophobic Mofsmentioning
confidence: 99%